2013 International Conference on Renewable Energy Research and Applications (ICRERA) 2013
DOI: 10.1109/icrera.2013.6749936
|View full text |Cite
|
Sign up to set email alerts
|

A new control method for microgrid power management

Abstract: Microgrids are receiving tremendous attention due to increasing need to integrate Distributed Generations (DG) and to provide reliable power to critical loads. Proper power management in microgrid is required to regulate the system voltage and frequency, maintain power quality, and manage DGs. A microgrid system has been studied in this paper, which includes two natural gas generators, an energy storage device, solar PV, and a wind turbine. The DGs are modeled in details using PSCAD software and the practical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Various researches are going on the micro-grid power management issues. Several studies have been reported to balance the power in micro-grid in recent studies [13][14][15]. Power control and management in hybrid ac-dc micro-grid is discussed in [16].…”
mentioning
confidence: 99%
“…Various researches are going on the micro-grid power management issues. Several studies have been reported to balance the power in micro-grid in recent studies [13][14][15]. Power control and management in hybrid ac-dc micro-grid is discussed in [16].…”
mentioning
confidence: 99%
“…Thereby, to successfully integrate DERs units in the power system, many technical challenges must be overcome to ensure that high levels of efficiency and reliability will be fully harnessed. In this sense, some of the main challenges are related to [21], [22]:…”
Section: Hierarchical Controlmentioning
confidence: 99%